Incidental Detection of Thyroid Nodule on Carotid Color Doppler Ultrasound in Patients Presenting with Cerebrovascular Diseases - Mazhar Shafiq; Shumaila; Tariq Jaffar; Sadaf Saleem; Akhter; Farrukh Nadeem; Muhammad Ali Mazhar (Pakistan Journal of Medicine and Dentistry, 2024)
Background: Thyroid nodules are often detected in clinical practice, during physical examination, or accidentally during different imaging techniques. Most of these nodules are characterized as benign, and thyroid cancer is identified in only a small subclass. Ultrasonography is considered an important tool in thyroid nodule evaluation. Therefore, the study aimed to determine the frequency of incidental detection of a nodule of thyroid on carotid color Doppler ultrasound in patients presenting with cerebrovascular diseases.